2018
DOI: 10.1080/13102818.2018.1474137
|View full text |Cite
|
Sign up to set email alerts
|

Short-term mutagenicity test by using IRAP molecular marker in rice grown under herbicide treatment

Abstract: Rice is an economically important plant as well as a model organism. The rice genome consists of 35% retrotransposons. Although most of the retrotransposons are inactivated through evolutionary processes, they can be activated under various biotic and abiotic stress conditions. The main objective of this study was to explore the effects of herbicides on retrotransposon activities and the usage of retrotransposons in short-term mutagenicity tests. In this study, bentazone and an MCPA (2-methyl-4-chlorophenoxyac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Meyer and Purugganan (2013) reported 60 genes related to plant domestication and breeding and concluded that 15% of them comprise transposable element insertions which have important effects. Therefore, there are many reports to determine polymorphism among species, role of transposon effects on biotic/abiotic stresses and evolutionary relationships (Yilmaz et al, 2018;Lanciano and Mirouze, 2018;Kalendar et al, 2019;Marakli et al, 2019). Furthermore, retrotransposons are valuable sources of molecular markers because of ubiquity, abundance, dispersion, and dynamism (Kalendar et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Meyer and Purugganan (2013) reported 60 genes related to plant domestication and breeding and concluded that 15% of them comprise transposable element insertions which have important effects. Therefore, there are many reports to determine polymorphism among species, role of transposon effects on biotic/abiotic stresses and evolutionary relationships (Yilmaz et al, 2018;Lanciano and Mirouze, 2018;Kalendar et al, 2019;Marakli et al, 2019). Furthermore, retrotransposons are valuable sources of molecular markers because of ubiquity, abundance, dispersion, and dynamism (Kalendar et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Retrotransposons enhance the likelihood of mutations and recombination, which allow the organism to exist in extreme conditions ( Galindo-Gonzalez et al, 2017 ). Molecular markers based on interspersed repeats have been efficiently used on rare or endemic plant species whose genomes have not been studied ( Kalendar & Schulman, 2013 ; Kalendar et al, 2019 ; Milovanov et al, 2019 ) and have also been widely used on a wide range of plants (both monocotyledons and dicotyledonous ( Abdollahi Mandoulakani et al, 2015 ; Nie et al, 2019 ; Vuorinen et al, 2018 ; Woodrow et al, 2010 ; Yilmaz et al, 2018 )) and in animals and fungi ( Turzhanova et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Polysaccharides extracted from C. pilosula cultivated in Gansu province have been appeared to have a functional property of encouraging spleen cells to produce antibodies and to prevent the production of serum hemolysis in ordinary mice while restoring serum antibody concentrations and antibodies to spleen cells in immunosuppressed mice (12), and it could be a promising therapeutic candidate for Alzheimer's disease (18). Plant medicines play a significant role as a substitutes for manufactured pharmaceuticals, reaching $115 billion by 2020 (19). The supply for herbal medicines is growing daily because they have a greater safety margin than synthetic drugs, therefore, characterizing medicinal herbs is an essential issue (20).…”
Section: Importance Of Codonopsis As a Medicinal Plantmentioning
confidence: 99%